Floating water treatment device using zeolite as adsorbent material - Zahari N.M.; Lok L.K.; Zawawi M.H.; Sidek L.M.; Mohamad D.; Ramli M.Z.; Haron S.H.; Nazmi I.; Hassan M.; Isa R.M.; Bahrin S.Z.A.S.K.; Helmi M. (American Institute of Physics Inc., 2023)
Pollution of water usually causes by anthropogenic influences like human activities and there have many ways to resolve this problem. By point source, illegal polluted water discharges from the industries to the river or by non-point source pollutants that emitted from multiple sources such as runoff of agricultural or urban area. The aquatic ecosystem will strictly affected by the polluted of river water which contained chemical substances. This project is design Floating Water Treatment Device using a zeolite as main absorbtion material to treat the polluted water. Water samples are taking from actual lake. Five physical water quality parameters were used to determine the removal efficiency such as Color, pH, BOD, Turbidity and TSS. The water quality result will be analyzed to determine the percent removal by the zeolite. Result shows using zeolite as absorbent had a potential to remove pollutant with 91% TSS removal. 2018 Author(s).